2022
DOI: 10.3389/fnut.2022.1073071
|View full text |Cite
|
Sign up to set email alerts
|

Structural, antioxidant, and immunomodulatory activities of an acidic exopolysaccharide from Lactiplantibacillus plantarum DMDL 9010

Abstract: This study investigated the structural, antioxidant, and immunomodulatory activities of acidic exopolysaccharide (EPS-LP2) isolated from Lactiplantibacillus plantarum DMDL 9010. EPS-LP2 is composed of fucose (Fuc), arabinose (Ara), galactose (Gal), glucose (Glc), mannose (Man), and D-fructose (Fru) with a molar ratio of 0.13: 0.69: 8.32: 27.57: 62.07: 0.58: 0.46, respectively. Structural analysis of EPS-LP2 exhibited a smooth irregular lamellar surface, rod-like structure with swollen ends and slippery surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the presence of EPS-LP2, ROS, MDA, and LDH contents were reduced in a dose-dependent manner. EPS-LP2 could also protect cells against H2O2-induced oxidative stress by improving SOD, CAT, and GSH-Px activities [150] .…”
Section: Mtcc 9510mentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of EPS-LP2, ROS, MDA, and LDH contents were reduced in a dose-dependent manner. EPS-LP2 could also protect cells against H2O2-induced oxidative stress by improving SOD, CAT, and GSH-Px activities [150] .…”
Section: Mtcc 9510mentioning
confidence: 99%
“…These findings suggest that the EPS obtained from L. plantarum C88 could enhance both enzymatic and non-enzymatic antioxidant activities as well as mitigate lipid peroxidation. It was reported that acidic exopolysaccharide (EPS-LP2) isolated from Lactiplantibacillus plantarum DMDL 9010 improved the enzymatic antioxidant activity, alleviated the reduction of antioxidant substances, and enhanced the non-enzymatic antioxidant system, leading to a reduction of the cell damage [150] . In the presence of EPS-LP2, ROS, MDA, and LDH contents were reduced in a dose-dependent manner.…”
Section: Mtcc 9510mentioning
confidence: 99%